2020
DOI: 10.1177/1756284820977693
|View full text |Cite
|
Sign up to set email alerts
|

Survival benefits from adjuvant transcatheter arterial chemoembolization in patients undergoing liver resection for hepatocellular carcinoma: a systematic review and meta-analysis

Abstract: Background: Although adjuvant transcatheter arterial chemoembolization (TACE) has been used to prevent recurrence after surgery in patients with hepatocellular carcinoma (HCC), the survival benefits from adjuvant TACE remain controversial. We sought to systematically evaluate the data on the effectiveness of adjuvant TACE for HCC, as well as identify patient populations that might benefit from adjuvant TACE. Methods: The PubMed, Embase, Medline and Cochrane library were systematically searched for studies publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 56 publications
0
38
0
Order By: Relevance
“…167 A recent systemic review and meta-analysis containing 24 studies (RCT=9; NRCT=15; n=6,977) demonstrated that adjuvant TACE was associated with a better OS (based on n=6,573; RCT=6; NRCT=15) and better DFS (based on n=2,260; RCT=7; NRCT=6) than LR alone for HCC patients. 171 In subgroup analyses, the pooled results revealed that adjuvant TACE was associated with an improved OS and DFS in the patients with multinodular HCC (HR=0.79 and 0.31, both P<0.01), MVI (HR=0.62 and 0.67, both P<0.01), or PVTT (HR=0.49 and 0.58, both P<0.01), but not among the patients with large HCC 5 cm). Furthermore, the pooled analysis of all the studies demonstrated that patients who underwent surgery followed by adjuvant TACE had better 1-, 3-, and 5-year survival versus surgery alone.…”
Section: Surgery Plus Adjuvant and Neoadjuvant Therapymentioning
confidence: 88%
See 2 more Smart Citations
“…167 A recent systemic review and meta-analysis containing 24 studies (RCT=9; NRCT=15; n=6,977) demonstrated that adjuvant TACE was associated with a better OS (based on n=6,573; RCT=6; NRCT=15) and better DFS (based on n=2,260; RCT=7; NRCT=6) than LR alone for HCC patients. 171 In subgroup analyses, the pooled results revealed that adjuvant TACE was associated with an improved OS and DFS in the patients with multinodular HCC (HR=0.79 and 0.31, both P<0.01), MVI (HR=0.62 and 0.67, both P<0.01), or PVTT (HR=0.49 and 0.58, both P<0.01), but not among the patients with large HCC 5 cm). Furthermore, the pooled analysis of all the studies demonstrated that patients who underwent surgery followed by adjuvant TACE had better 1-, 3-, and 5-year survival versus surgery alone.…”
Section: Surgery Plus Adjuvant and Neoadjuvant Therapymentioning
confidence: 88%
“…The pooled HR for OS and DFS for all studies was in favor of adjuvant TACE after surgical resection. 171 A recent meta-analysis reported that sorafenib as adjuvant therapy after liver resection was associated with improved OS (hazard ratio=0.71, 95% CI=0.59-0.86; P<0.001), RFS (hazard ratio=0.68, 95% CI=0.54-0.86, P=0.001) and lower recurrence rate (pooled risk ratio=0.78, 95% CI=0.68-0.90, P<0.001) without unbearable side-effects. 172 The treatment options for the HCC patients with PVTT are listed in Figure 3.…”
Section: Surgery Plus Adjuvant and Neoadjuvant Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Longterm prognosis after HCC resection is, however, still poor due to the high incidence of recurrence [3][4][5]. Transcatheter arterial chemoembolization (TACE) has been used in the postoperative setting as a means to decrease risk of recurrence and improve survival [6][7][8]. Whereas, in clinical practice, controversy persists relative to the role of adjuvant TACE for resected HCC [9][10][11].…”
mentioning
confidence: 99%
“…A retrospective study by propensity score matching, which included 464 patients with HCC and PVTT indicated that PA-TACE has better MST compared with surgery alone, especially for type II/III PVTT according to Cheng's classification (21). A subgroup analysis of systemic review and metaanalysis revealed that adjuvant TACE following surgery is associated with improved disease-free survival (DFS) and overall survival (OS) compared with surgery alone (22). However, subgroup analysis of the meta-analysis included only one RCT and one NRCT, allowing the adjuvant role of TACE to be controversial.…”
Section: Multidisciplinary Management Program Of Hepatocellular Carcinomamentioning
confidence: 99%